The relationship between carbohydrate intake and sleep patterns - Zhao, Yan; Guo, Hailong (Frontiers in Nutrition, 2024)
Background: A healthy dietary habit may contribute to good sleep quality. The present study investigates the correlation between the quality and quantity of daily carbohydrate consumption and poor sleep patterns. Methods: The exposures of interest included low- and high-quality carbohydrate consumption and total daily carbohydrate consumption. Subjects were classified into four different carbohydrate consumption patterns: Pattern 1 was characterized by high-quality carbohydrates below the median and low-quality carbohydrates above the median; Pattern 2 included both high- and low-quality carbohydrates below the median; Pattern 3 was defined as high- and low-quality carbohydrates above the median; Pattern 4 referred to high-quality carbohydrates above the median and low-quality carbohydrates below the median. The comprehensive sleep patterns included three different sleep behaviors: sleep duration, daytime sleepiness, and snoring, which were used to score sleep patterns. A score ranging from 0 to 1 was classified as having a healthy sleep pattern, while a score between 2 and 3 showed poor sleep patterns. Survey-weighted multivariable logistic regression analyses were adopted. Results: In the multivariate analysis, individuals who consumed more high-quality carbohydrates were linked to a decreased likelihood of experiencing poor sleep patterns (odds ratio (OR) 0.71; 95% confidence interval (CI) 0.62-0.81), while increased consumption of low-quality carbohydrates (OR 1.39; 95%CI 1.20-1.61) and total daily carbohydrates (OR 1.31; 95%CI 1.10-1.57) was related to an elevated risk of poor sleep patterns. Participants who adhered to carbohydrate intake pattern 4 exhibited a 36% lower risk of poor sleep patterns than those who followed carbohydrate intake pattern 1 (OR 0.64; 95%CI 0.56-0.74). There was a positive correlation between elevated added sugar consumption and an increased probability of developing poor sleep patterns. In contrast, an elevated intake of whole grains, fruits, or non-starchy vegetables was related to a decreased likelihood of experiencing poor sleep patterns. Conclusions: The increased consumption of low-quality carbohydrates may heighten the susceptibility to poor sleep patterns, whereas the increased consumption of high-quality carbohydrates may mitigate the risk of developing poor sleep patterns.